2011
DOI: 10.1038/bmt.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Indolent T-cell large granular lymphocyte leukaemia after haematopoietic SCT: a clinicopathologic and molecular analysis

Abstract: Four women and three men after allogeneic (n ¼ 4) and autologous (n ¼ 3) haematopoietic SCT (HSCT) were observed to have an increase in T-cell large granular lymphocytes (T-LGLs) of CD3 þ CD8 þ phenotype for a median of 41 (15 --118) months. Clonal rearrangement of the T-cell receptor gene was verified by two PCR techniques and direct DNA sequencing, confirming that the cases were neoplastic and therefore classifiable as T-LGL leukaemia. In the allogeneic HSCT cases, T-LGL leukaemia was derived from donor T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 21 publications
(21 reference statements)
2
31
0
4
Order By: Relevance
“…This observation is consistent with a recent study of EATL in 18 Chinese patients, which also showed only type II histology [10]. In several previous studies of intestinal T-cell lymphomas in Asian patients [6][7][8][9]11,12,17,18], type II EATL was also predominantly observed, although fewer than 10 cases of apparently classical EATL were described. However, the diagnosis of classical EATL in these few cases had been queried, based on the lack of stringency in diagnosis, doubtful histologic features, and immunophenotypes that would in fact be consistent with type II EATL [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with a recent study of EATL in 18 Chinese patients, which also showed only type II histology [10]. In several previous studies of intestinal T-cell lymphomas in Asian patients [6][7][8][9]11,12,17,18], type II EATL was also predominantly observed, although fewer than 10 cases of apparently classical EATL were described. However, the diagnosis of classical EATL in these few cases had been queried, based on the lack of stringency in diagnosis, doubtful histologic features, and immunophenotypes that would in fact be consistent with type II EATL [10].…”
Section: Discussionsupporting
confidence: 92%
“…Other additional markers were performed according to the discretion of the reporting histopathologists. Epstein-Barr Virus (EBV)-encoded RNA (EBER) was detected by in situ hybridization (ISH), and T-cell receptor (TCR) gene clonal rearrangement by polymerase chain reaction (PCR) as previously reported [12].…”
Section: Methodsmentioning
confidence: 91%
“…No acute graft-versus-host disease (GVHD) occurred. Despite the apparent successful haematopoietic engraftment three months post-HSCT, DNA chimerism studies of peripheral blood with short tandem repeat analysis [1] showed only 33% donor chimerism. Expectedly, plasma fluorescence emission scanning still showed an abnormal peak.…”
Section: To the Editormentioning
confidence: 95%
“…Among patients undergoing allo-HCT, T-LGL lymphoproliferation can be either asymptomatic 1,4 or accompanied by cytopenias and autoimmune manifestations. 2 Here, both patients experienced unexplained neutropenia persisting for several months; immunology and virology were negative, while the rapid onset of neutropenia after the first administration of Rituximab precluded the diagnosis of the recently recognized syndrome of Rituximab-associated late-onset neutropenia.…”
Section: T-cell Receptor B-chain Gene Repertoire Analysismentioning
confidence: 99%